An Econometric Analysis of Efficiency and Loan Loss Provisioning Behaviour in German Banking - Bochert, Carsten (2016)
This study examines the loan loss provisioning behaviour of the German banking industry by using a sample of 52 commercial banks over the period of 2007-2014. It investigates the relationship between loan loss provisions and the business cycle as well as the income smoothing and capital management hypotheses. In addition, the relationship between the bank’s loan loss provisioning behaviour and their efficiency is examined. This study conducts a two stage analysis: First, the efficiency levels of the banks are estimated from a translog cost function. Then, the estimated efficiency scores are incorporated into the regression of loan loss provisions using Generalized Method of Moments (GMM) estimators.